2006
DOI: 10.1302/0301-620x.88b9.17500
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoresis of antibiotics into segmental allografts

Abstract: Iontophoresis is a novel technique which may be used to facilitate the movement of antibiotics into the substance of bone using an electrical potential applied externally. We have examined the rate of early infection in allografts following application of this technique in clinical practice. A total of 31 patients undergoing revision arthroplasty or surgery for limb salvage received 34 iontophoresed sequential allografts, of which 26 survived for a minimum of two years. The mean serum antibiotic levels after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Two prospective cohort and one randomized trial were classified as level II evidence, whereas the remaining seven reports performed retrospective chart reviews or cohort studies (level III evidence) (Galia et al 2009; Guo et al 2012; Khoo et al 2006; Krasny et al 2013; Pruss et al 2002). Using the GRADE assessment, the quality of clinical studies according to the objectives was found to range from very low to high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prospective cohort and one randomized trial were classified as level II evidence, whereas the remaining seven reports performed retrospective chart reviews or cohort studies (level III evidence) (Galia et al 2009; Guo et al 2012; Khoo et al 2006; Krasny et al 2013; Pruss et al 2002). Using the GRADE assessment, the quality of clinical studies according to the objectives was found to range from very low to high.…”
Section: Resultsmentioning
confidence: 99%
“…The source of the infection was not stated. One was resolved by treatment with antibiotics, and another required amputation (Khoo et al 2006). The GRADE quality of the clinical evidence was low to moderate.…”
Section: Resultsmentioning
confidence: 99%
“…These capacities make them more attractive for local therapy and allow using uncemented implants. If cortical bone should become preferable out of whatever circumstances it can be loaded with antibiotics as well [21]. Using adequate impregnation techniques antibiotics may elute in a similarly effective way as with cancellous bone [22].…”
Section: Discussionmentioning
confidence: 99%
“…The groups of Michalak and Khoo tried to increase concentrations of gentamicin and flucloxacillin, respectively, inside segmental allografts by using iontophoresis. Although the reported antibiotic concentrations in drainage fluid were inferior to those presented in combination with purely cancellous grafts, none of the patients became re-infected after implantation of the iontophoresed segmental grafts [20,21]. However, all groups have used the grafts only in the second stage of a two-stage revision after resolution of clinical, laboratory and radiological evidence of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Buttaro et al (23) favorably used vancomycin supplemented cancellous grafts for reconstruction after infected THA (20,23 (24,25). However, all these groups used antibiotic impregnated grafts only in the second stage of a two-stage revision, after resolution of clinical and laboratory evidence of infection.…”
Section: Justificationmentioning
confidence: 99%